THE ROLE AND PLACE OF PROVERBS AND SAYINGS IN THE SYSTEM OF LANGUAGE AND THEIR LINGUISTIC FEATURES (E Conference Zone, 2022)
This article explores different points of view on the interpretation of the concepts of "proverb" and "saying" in modern linguistics.